2020
DOI: 10.1021/acs.jmedchem.0c00770
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Plasticity in the Active Site of Protein N-terminal Methyltransferase 1 Using Bisubstrate Analogues

Abstract: The bisubstrate analogue strategy is a promising approach to develop potent and selective inhibitors for protein methyltransferases. Herein, the interactions of a series of bisubstrate analogues with protein N-terminal methyltransferase 1 (NTMT1) were examined to probe the molecular properties of the active site of NTMT1. Our results indicate that a 2-C to 4-C atom linker enables its respective bisubstrate analogue to occupy both substrate- and cofactor-binding sites of NTMT1, but the bisubstrate analogue with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…27 Previous studies demonstrated that NAH-C4-GPKRIA and NAH-C4-GPKR bisubstrate analogs containing a 4-C carbon link showed slightly higher potency than those with a 3-C atom linker. 25 However, the NAH-C3-GPKK bisubstrate analogue 1 with the 3-C atom linker (Ki, app = 7 ± 1 nM) exhibited similar inhibition as its 4-C linker analogue 2 (Ki, app = 5.0 ± 0.3 nM) (Table 1). Likewise, the NAH-C3-GPK bisubstrate analogue 3 with a 3-C carbon linker showed comparable inhibitory activity to compound 4 with a 4-C carbon linker, although the Ki, app values of 3 and 4 were increased by 6-8 fold compared to 1 and 2 due to the shortened peptide moiety from a tetrapeptide to a tripeptide.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…27 Previous studies demonstrated that NAH-C4-GPKRIA and NAH-C4-GPKR bisubstrate analogs containing a 4-C carbon link showed slightly higher potency than those with a 3-C atom linker. 25 However, the NAH-C3-GPKK bisubstrate analogue 1 with the 3-C atom linker (Ki, app = 7 ± 1 nM) exhibited similar inhibition as its 4-C linker analogue 2 (Ki, app = 5.0 ± 0.3 nM) (Table 1). Likewise, the NAH-C3-GPK bisubstrate analogue 3 with a 3-C carbon linker showed comparable inhibitory activity to compound 4 with a 4-C carbon linker, although the Ki, app values of 3 and 4 were increased by 6-8 fold compared to 1 and 2 due to the shortened peptide moiety from a tetrapeptide to a tripeptide.…”
Section: Resultsmentioning
confidence: 94%
“…The proposed 1-4 were synthesized in a convergent manner by reacting the primary amines (7-8) with α-bromo peptide on resin and followed by acid treatment as described before (Schemes 1). 23,25 Inhibition Evaluation. The inhibitory activities of compounds 1-4 against NTMT1 were evaluated in the SAH hydrolase (SAHH)-coupled fluorescence assay under the condition that both SAM and the peptide substrate GPKRIA were at their respective Km values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations